Respostas

A melhor resposta!
2014-09-01T14:20:42-03:00
Y=3x-2      ai é so substituir o x pelo numero da tabela por exemplo      y=3(-3)-2  =  -9 -2 = -11  vou colocar o restante das respostas                          -3 = -11                                                                                                                -2 = -9                                                                                                                                 -1 = -5                                                                                                                                  0 = -2                                                                                                                                  1 =  1                                                                                                                                  2 =  4                                                                                                                    
2 5 2